Dramaturgi Komunikasi Politik Konten Instagram @bestiputri pada PILKADA 2024 - Novia Trias Amanda Permana; Acmad Wildan Kurniawan; Iis Zilfah Adnan (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Social media, especially Instagram, is now the main tool for politicians to build public image and communication, especially ahead of the 2024 Regional Elections in Garut. Princess Karlina uses Instagram to display her personal and campaign side, analyzed with Goffman's dramaturgy theory highlighting front and back stage strategies in shaping an authentic political image. This study uses a descriptive qualitative method with an analysis of the content of @bestiputri Instagram uploads and in-depth interviews with account managers. Each upload is analyzed based on visual, narrative, and audience interaction elements, and then categorized as a front or back stage to understand @bestiputri digital political communication strategy holistically. The front stage contains formal activities and campaigns, while the back stage displays a personal side. Image-damaging elements are hidden, so Instagram becomes a performance arena for shaping public opinion and emotional closeness to Instagram voters is effectively used @bestiputri to build and manage self-image through front and back stage strategies. The dramaturgical approach allows politicians to organize their presentations, choosing what is shown, thus emphasizing the strategic role of social media in local political campaigns and showcasing the involvement of women politicians in the digital space.